2020
DOI: 10.1097/md.0000000000023323
|View full text |Cite
|
Sign up to set email alerts
|

Damage control surgery for the treatment of perforated acute colonic diverticulitis

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 35 publications
0
6
0
9
Order By: Relevance
“…There is some evidence that supports the use of this surgical strategy in non-traumatic surgical emergencies, such as perforated acute diverticulitis. DCS includes an abbreviated source-control laparotomy with a vacuum-assisted temporary abdominal closure device, followed by transfer to the Intensive Care Unit for resuscitation, with or without second-look laparotomy, and delayed definitive surgical repair [ 57 , 58 ]. A systematic review of 8 trials (7 retrospective and 1 prospective) between 2006 and 2018 evaluated the indications for and outcomes related to DCS for perforated acute diverticulitis.…”
Section: Management Of Complicated Diverticulitismentioning
confidence: 99%
See 1 more Smart Citation
“…There is some evidence that supports the use of this surgical strategy in non-traumatic surgical emergencies, such as perforated acute diverticulitis. DCS includes an abbreviated source-control laparotomy with a vacuum-assisted temporary abdominal closure device, followed by transfer to the Intensive Care Unit for resuscitation, with or without second-look laparotomy, and delayed definitive surgical repair [ 57 , 58 ]. A systematic review of 8 trials (7 retrospective and 1 prospective) between 2006 and 2018 evaluated the indications for and outcomes related to DCS for perforated acute diverticulitis.…”
Section: Management Of Complicated Diverticulitismentioning
confidence: 99%
“…A systematic review of 8 trials (7 retrospective and 1 prospective) between 2006 and 2018 evaluated the indications for and outcomes related to DCS for perforated acute diverticulitis. They found that patients treated with DCS had a lower percentage of overall morbidity, 30-day mortality, and definitive ostomy compared to those treated with Hartman’s procedure [ 58 ]. Based on the 2016 WSES Guidelines, DCS remains an effective surgical strategy in critically ill patients affected by sepsis/septic shock and hemodynamic instability.…”
Section: Management Of Complicated Diverticulitismentioning
confidence: 99%
“…A CCD proporciona redução significativa no tempo cirúrgico, na gravidade do caso em que o paciente se encontra e na duração da resposta em uma doença inflamatória sistêmica subsequente, com impacto direto na mortalidade. 22 Diante disso, foi possível observar redução da mortalidade de 58% para 33% no ano de 2001 e de 27% para 10% em 2006. 23 Na atualidade, técnicas de fechamento temporário da cavidade abdominal com menor tensão como a VAC, Bolsa de Bogotá e Vacuum-pack oferecem maiores vantagens, como o baixo custo e acesso fácil ao material, quando comparadas a CCD, quando essa envolve peritoneostomia, que frequentemente resulta em retração da aponeurose e perda da capacidade de fechar a parede abdominal, ocasionando a formação de hérnias ventrais incisionais.…”
Section: Impactos Do Damage Control Abdominalunclassified
“…Ao longo do tempo, as etapas da cirurgia de controle de danos foram sendo aprimoradas de acordo com sua prática, benefícios e falhas 1,2 . Atualmente, ela é dividida em cinco passos, sendo esses: a seleção do paciente; cirurgia inicial e abreviada;…”
Section: Introductionunclassified